Menispermaceae Juss. para a flora da Bahia, Brasil - Teixeira, Michella Del Rei (2012)
A floristic survey of Menispermaceae in Bahia, Brazil is presented as a contribution to the study of the flora in the state. Twenty-two taxa are recognized and an analytical key of identification, descriptions, comments, distributions maps and illustrations of the same are provided. Are provided for the first time the description and illustration of characters reprodutive of the Curarea crassa (♀), Odontocarya duckei (♂) and Sciadotenia pubistaminea (fruit). Abuta selloana e Disciphania ernstii are cited for the first time for the Bahia. One species of Cissampelos remains unidentified, but the morphological affinities with other species are discussed.